1998
DOI: 10.1161/01.cir.97.17.1731
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Blockade Inhibits Activation of Mitogen-Activated Protein Kinases in Rat Balloon-Injured Artery

Abstract: Background-The effect of balloon injury on the arterial signal transduction pathway has not been examined. In vitro studies show that extracellular signal-regulated kinases (ERKs) and c-Jun NH 2 -terminal kinases (JNKs), belonging to the mitogen-activated protein kinase (MAPK) family, play a critical role in the activation of transcription factor activator protein-1 (AP-1) and cell proliferation or apoptosis. However, the activation and role of MAPKs in vascular diseases in vivo remain to be determined. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 43 publications
1
66
0
2
Order By: Relevance
“…16 However, the biological role of AP-1 in vascular SMC remains to be determined. We and other groups of investigators have previously reported that AP-1-binding activity, composed of c-Jun, is significantly enhanced in injured rat artery by balloon angioplasty, the elevation of blood pressure, or angiotensin II infusion, [11][12][13][14] suggesting that AP-1 containing c-Jun may play some role in various vascular diseases. These findings encouraged us to examine the role of AP-1 in vascular SMC proliferation and intimal hyperplasia in injured artery, by gene transfer of dominant negative mutant of c-Jun.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…16 However, the biological role of AP-1 in vascular SMC remains to be determined. We and other groups of investigators have previously reported that AP-1-binding activity, composed of c-Jun, is significantly enhanced in injured rat artery by balloon angioplasty, the elevation of blood pressure, or angiotensin II infusion, [11][12][13][14] suggesting that AP-1 containing c-Jun may play some role in various vascular diseases. These findings encouraged us to examine the role of AP-1 in vascular SMC proliferation and intimal hyperplasia in injured artery, by gene transfer of dominant negative mutant of c-Jun.…”
Section: Discussionmentioning
confidence: 75%
“…9,10 Recently, AP-1 has been reported to be rapidly activated in balloon-injured artery and this activated AP-1 contained c-Jun, 11 and similar findings have been also obtained by our recent work. 12 Furthermore, in rats, vascular AP-1, composed of c-Jun, is also significantly activated in vivo by acute hypertension or angiotensin II administration. 13,14 However, the significance of AP-1 for vascular diseases remains to be defined, mainly because of the lack of the specific and potent pharmacological inhibitor of AP-1.…”
Section: Of Dn-c-jun Was Examined On Balloon Injury-induced Intimal Hmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Ex vivo tissue samples were immediately frozen at À801C after dissection. Frozen tissue was homogenized by thawing the samples in an appropriate volume of the lysis buffer, followed by disruption with a polytron homogenizer.…”
Section: Western Blot Analysismentioning
confidence: 99%